A research agenda for evaluating living labs as an open innovation model for environmental and agricultural sustainability - Christine Beaudoin (Environmental Challenges, 2022)
The magnitude of environmental challenges we are facing today requires the involvement of a diversity of stakeholders and collaborators to develop socially, culturally, and economically robust sustainability practices. Living labs catalyse the development of user-centric solutions for complex environmental issues by exploring, co-creating, testing, and evaluating innovations within real-world contexts. The living lab approach is relatively new in the environmental and agricultural sectors but is quite well established in many areas such as information and communication technology. For living labs to play a greater role in environmental sustainability, we present a research agenda related to the evaluation and effectiveness of living labs in the context of environmental and agricultural sustainability. We refer to evaluation as the act of assessing the process and outcomes of a living lab, and effectiveness as the level to which a living lab is successful in achieving a certain desirable process or outcome. Our research agenda is based on empirical research using an adapted Delphi method – a process to iteratively gather input from a panel of experts – involving a total of 44 researchers and experts in the domains of living labs, evaluation methods, and agro-environmental issues. The resulting integrated research agenda identifies important gaps in both research and practice to improve the impact of living labs. Our findings highlight the need to better understand effective use of this collaborative, open innovation approach in research and management focused on environmental and agricultural sustainability. Future research should investigate the knowledge gaps for we have identified in terms of diversity of stakeholders, key dimensions of evaluation and how to enable effectiveness of living labs.